Analisis Human Error Pada Surat Penyerahan Petikemas (SP2) Dan Warehouse Management System (WMS) - Somadi Somadi; Indani Zulfah (Competitive, 2021)
PT. XYZ is a logistics service company engaged in the shipping service business of sea / air ships (EMKL / EMKU) and warehousing / warehousing. In the operational field of Full Container Load (FCL) at PT XYZ, there are problems, namely Human Error (Human Error) inputting data into the Container Handover Letter (SP2) and Warehouse Management System (WMS) documents. The purpose of this study was to determine the causative factors and to find out the right recommendations for improvement in the event of data input errors in the WMS system and data input errors in the manufacture of SP2. Data collection techniques, namely by observation and interviews. The analysis technique used fishbone diagrams and 5W + 1H analysis. Factors that cause Human Error are lack of training or trainning, the number of other tasks outside the job description, the absence of work shifts, the atmosphere is too busy by EMKL who takes care of documents, and the absence of an RFID Reader. To minimize the occurrence of Human Errors is to hold training and provide motivation so that employees can take part in training in operating the WMS system, socializing and providing additional benefits or money to employees, recruiting new employees at least divided into 2 team work shifts for the WMS operation section, adding service into two parts, will reduce EMKL queues and speed up document input to WMS, conduct socialization to use RFID.